Keterkaitan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Jasa Tranportasi Ojek Online Di Samarinda - Sattar Sattar; Saiful Saiful; Angga Kusumah; La Nggedo (Universitas Mercu Buana, 2022)
This study aims to analyze the relationship between service and customer satisfaction in online motorcycle taxi transportation services. This study uses five independent variables, namely reliability, responsiveness, assurance, empathy and tangible with one dependent variable, namely customer satisfaction. After conducting a literature and field review and formulating hypotheses, the data in this study were collected by distributing questionnaires to 72 people who had used online motorcycle taxi transportation services as research samples. The sampling technique used is purposive sampling. The data analysis method used is quantitative analysis, namely validity and reliability test, classical assumption test, multiple linear regression analysis, t test, f test, coefficient of determination. Based on data analysis, the results of the study indicate that the indicators in this study are valid and reliable. In the classical assumption test, the data is normally distributed, there is a linear relationship and there is no heterogenetic. In testing the hypothesis that service quality has a positive effect on customer satisfaction.Keywords: Service Quality, Consumer Satisfaction